Electrochemical aptamer-based biosensor developed to monitor PSA and VEGF released by prostate cancer cells - Crulhas, Bruno P. [UNESP]; Karpik, Agnieszka E. [UNESP]; Delella, Flávia K. [UNESP]; Castro, Gustavo R. [UNESP]; Pedrosa, Valber A. [UNESP] (Springer Nature, 2017)
Early prostate cancer (PCa) diagnostic is crucial to enhance patient survival rates; besides, non-invasive platforms have been developed worldwide in order to precisely detect PCa biomarkers. Therefore, the aim of the present study is to develop a new aptamer-based biosensor through the self-assembling of thiolated aptamers for PSA and VEGF on the top of gold electrodes. This biosensor was tested in three prostate cell lines (RWPE-1, LNCaP and PC3). The results evidenced a stable and sensitive sensor presenting wide linear detection ranges (0.08–100 ng/mL for PSA and 0.15 ng–100 ng/mL for VEGF). Therefore, the aptasensor was able to detect the patterns of PSA and VEGF released in vitro by PCa cells, which gave new insights about the prostate cancer protein dynamics. Thus, it could be used as a non-invasive PCa clinical diagnosis instrument in the near future.
Keywords: Aptasensor; Biomarkers; In vitro experiments; Protein released by cancer cell